Dissenting Opinion of Corruption Court Judges as a Form of Freedom and Legal Reform in Indonesia - Simanjuntak, Louis Fernando; Rusmiati, Elis; Atmaja, Budi Arta (Faculty of Law, Universitas Lampung, 2023)
The existence of dissenting opinions is a step in organizing law enforcement. This is also an important issue in organizing judicial power in relation to the 1945 Constitution and Law No. 48/2009 on Judicial Power. In Indonesia itself, judges are allowed to give dissenting opinions, although there has never been a clear definition of dissenting opinions. In Anglo-Saxon law, dissenting opinions have become commonplace, and these dissenting opinions often form new laws. This is in line with the term